Sustainability: An Introduction View from ICIEOM - Lima, Rui M. (2012)
This Special Issue of the Brazilian Journal of Operations and Production Management (BJOPM) features four papers selected from the XVIII International Conference on Industrial Engineering and Operations Management (ICIEOM), which conference theme was “Sustainability”, and two invited papers based on keynote speeches regarding Sustainability and its association to Industrial Engineering fields (one from ICIEOM and the other from the ENEGEP conference). This editorial paper evaluates and summarizes these selected contributions as well as introduces the term sustainability.